Design, synthesis and molecular docking of novel triazole derivatives as potential CoV helicase inhibitors - Zaher Nashwa Hafez; Mostafa Mohammed Ismail; Altaher Abdullah Yousef (Acta Pharmaceutica)
Middle East respiratory syndrome coronavirus (MERS-CoV) had emerged and spread because of the worldwide travel and inefficient healthcare provided for the infected patients in several countries. Herein we investigated the anti-MERS-CoV activity of newly synthesized sixteen halogenated triazole compounds through the inhibition of helicase activity using the FRET assay. All new compounds underwent justification for their target structures via microanalytical and spectral data. SAR studies were performed. Biological results revealed that the most potent compounds were 4-(cyclopent-1-en-3-ylamino)-5-(2-(4-iodophenyl)hydrazinyl)-4H-1,2,4-triazole-3-thiol (16) and 4-(cyclopent-1-en-3-ylamino)-5-[2-(4-chlorophenyl)hydrazinyl]-4H-1,2,4-triazole-3-thiol (12). In silico molecular docking of the most potent compounds was performed to the active binding site of MERS-CoV helicase nsp13. Molecular docking results are in agreement with experimental findings.